I'm just a person - Notaro, Tig (Ecco, an imprint of HarperCollins Publishers, 2016)
In the span of four months in 2012, Tig Notaro was hospitalized for a debilitating intestinal disease called C-diff, her mother unexpectedly died, she went through a breakup, and she was diagnosed with bilateral breast cancer. Days after her diagnosis, Tig took her grief onstage, opening an unvarnished set with, "Good evening. Hello. I have cancer." The set went viral instantly and was later released as an album, Live, and was nominated for a Grammy. This book takes stock of that no good, very bad year, with an inspired combination of deadpan silliness and open-hearted vulnerability. A moving and often hilarious look at Notaro's journey into the darkness and her thrilling return from it.